Challenges Teaching in Kazakh as L2 - Gumarova, Lora (Nazarbayev University Graduate School of Education, 2017)
One of the most recent strategic developments of the country is language policy based on the cultural project “Trinity of Languages”. In education it is implemented as trilingual policy. The main focus of this qualitative master thesis is to explore geography teachers’ perceptions about challenges in teaching geography in Kazakh as L2 at Russian-medium groups (RMGs). This study can be a valuable contribution to language-in-education policy research and practices in Kazakhstani trilingual context at micro and macro levels of trilingual policy and planning. The research purpose is to explore teachers’ perceptions about facing challenges in teaching geography in Kazakh as L2 to RMGs, what practices they use to address the challenges in their classroom practices, and how teachers’ perceive the role of pupils’ environment in learning content in Kazakh as L2. Interviews, classroom observations and syllabi analyses were used to explore perceptions about L2 challenges of purposefully selected four teachers (two teachers in each selected NIS) from two parts of Kazakhstan (western and northern). The empirical findings showed unevenly developed Kazakh L2 proficiency, low academic vocabulary proficiency and learners’ environment perceived as major challenges. Based on the language-in education framework within community policy perspective NIS is significant L2 and L3 even L1 enhancement platform whereas home language environment seemed as challenge and benefits under certain circumstances. The least important issue is pronunciation in L2 in CLIL lessons. There is one challenge related to syllabi, as it was revealed both Kazakh and Russian medium classes use one syllabus with similar aims, outcomes, and materials. Teachers did not consider it as a problem. Locations of schools as a challenge were not proved. This study helps local policy experts understand teaching challenges in Kazakh as L2 based on the study framework. Одним из последних стратегических направлений развития страны является языковая политика, основанная на культурном проекте «Триединство языков». В образовании этот проект реализуется как политика трёхъязычия. Главная цель этой магистерской диссертации, основанной на качественном анализе, является изучение восприятия трудностей в преподавании географии на казахском языке, как на втором языке (Я2), в русскоязычном классе. Это исследование может стать ценным вкладом в политику исследования и практику казахстанского языкового образования в контексте трехъязычия. В работе анализируется восприятие учителями проблем, возникающих при обучении географии на казахском языке, как на втором языке, в русскоязычном классе; вместе с тем какие методы используют учителя - предметники для решения проблем в своей практике. Также анализируется как учителя воспринимают ученическую среду и её роль в изучении предметов на казахском языке как Я2. В ходе исследования, для сбора информации, были проведены полуформальные индивидуальные интервью, наблюдение уроков; был проанализирован утвержденный предметный план для изучения восприятия проблем Я2. Мною были целенаправленно выбраны четыре учителя НИШ двух регионов Казахстана (западной и северной части). Эмпирические данные выявили неравномерность развитий второго языка, низкий академический уровень владения лексикой, а ученическая среда русскоязычных классов воспринимается как серьезная проблема. Политика образования, как основа этого исследования, включает несколько политик сообщества НИШ и является основной средой или сообществом, где успешно развиваются Я2, Я3, а также Я1. Однако, другая (домашняя) языковая среда может быть рассмотрена и как проблема и как выгода в развитии Я2 в зависимости от определенных обстоятельств. Наименее важной проблемой является произношение в Я2 на уроках CLIL. В ходе сбора информации для данной работы было выявлено, что в параллелях, и с обучением на казахском языке и с обучением на русском языке, используется одна программа с одинаковыми целями, ожидаемыми результатами и материалами, что учителями географии не рассматривается как проблема. Географическое положение НИШ как проблема не была подтверждена. Предложенное исследование поможет местным экспертам образования понять трудности преподавания на казахском языке как на втором языке.
Keywords: language policy; trilingual policy; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education